In vitro autoradiography of receptor-activated G proteins in rat brain by agonist-stimulated guanylyl 5'-[gamma-[35S]thio]-triphosphate binding. - Sim, L J (1995)
Agonists stimulate guanylyl 5'-[gamma-[35S]thio]-triphosphate (GTP[gamma-35S]) binding to receptor-coupled guanine nucleotide binding protein (G proteins) in cell membranes as revealed in the presence of excess GDP. We now report that this reaction can be used to neuroanatomically localize receptor-activated G proteins in brain sections by in vitro autoradiography of GTP[gamma-35S] binding. Using the mu opioid-selective peptide [D-Ala2,N-MePhe4,Gly5-ol]enkephalin (DAMGO) as an agonist in rat brain sections and isolated thalamic membranes, agonist stimulation of GTP[gamma-35S] binding required the presence of excess GDP (1-2 mM GDP in sections vs. 10-30 microM GDP in membranes) to decrease basal G-protein activity and reveal agonist-stimulated GTP[gamma-35S] binding. Similar concentrations of DAMGO were required to stimulate GTP[gamma-35S] binding in sections and membranes. To demonstrate the general applicability of the technique, agonist-stimulated GTP[gamma-35S] binding in tissue sections was assessed with agonists for the mu opioid (DAMGO), cannabinoid (WIN 55212-2), and gamma-aminobutyric acid type B (baclofen) receptors. For opioid and cannabinoid receptors, agonist stimulation of GTP[gamma-35S] binding was blocked by incubation with agonists in the presence of the appropriate antagonists (naloxone for mu opioid and SR-141716A for cannabinoid), thus demonstrating that the effect was specifically receptor mediated. The anatomical distribution of agonist-stimulated GTP[gamma-35S] binding qualitatively paralleled receptor distribution as determined by receptor binding autoradiography. However, quantitative differences suggest that variations in coupling efficiency may exist between different receptors in various brain regions. This technique provides a method of functional neuroanatomy that identifies changes in the activation of G proteins by specific receptors.